Biogeography and Independent Diversification in the Protist Symbiont Community of Heterotermes tenuis - De Martini, Francesca; Coots, Nicole L.; Jasso-Selles, Daniel E.; Shevat, Jordyn; Ravenscraft, Alison; Stiblík, Petr; Šobotník, Jan; Sillam-Dussès, David; Scheffrahn, Rudolf H.; Carrijo, Tiago F.; Gile, Gillian H. (Frontiers in Ecology and Evolution, 2021)
The eukaryotic microbiome of “lower” termites is highly stable and host-specific. This is due to the mutually obligate nature of the symbiosis and the direct inheritance of protists by proctodeal trophallaxis. However, vertical transmission is occasionally imperfect, resulting in daughter colonies that lack one or more of the expected protist species. This phenomenon could conceivably lead to regional differences in protist community composition within a host species. Here, we have characterized the protist symbiont community of Heterotermes tenuis (Hagen) (Blattodea: Rhinotermitidae) from samples spanning South and Central America. Using light microscopy, single cell isolation, and amplicon sequencing, we report eight species-level protist phylotypes belonging to four genera in the phylum Parabasalia. The diversity and distribution of each phylotype’s 18S rRNA amplicon sequence variants (ASVs) mostly did not correlate with geographical or host genetic distances according to Mantel tests, consistent with the lack of correlation we observed between host genetic and geographical distances. However, the ASV distances of Holomastigotoides Ht3 were significantly correlated with geography while those of Holomastigotoides Ht1 were significantly correlated with host phylogeny. These results suggest mechanisms by which termite-associated protist species may diversify independently of each other and of their hosts, shedding light on the coevolutionary dynamics of this important symbiosis.